Biodegradable Facemasks: Biodegradable, Efficient, and Breathable Multi‐Use Face Mask Filter (Adv. Sci. 6/2021). Issue 6 (17th March 2021) - Choi, Sejin; Jeon, Hyeonyeol; Jang, Min; Kim, Hyeri; Shin, Giyoung; Koo, Jun Mo; Lee, Minkyung; Sung, Hye Kyeong; Eom, Youngho; Yang, Ho‐Sung; Jegal, Jonggeon; Park, Jeyoung; et al.
Abstract : In article number 2003155, Jeyoung Park, Dongyeop X. Oh, Sung Yeon Hwang, and co‐workers report a biodegradable, moisture‐resistant, highly efficient, and breathable face mask filter based on easy‐to obtain poly(butylene succinate) coated with chitosan nanowhiskers. Integrated microfiber/nanofiber mats present a particulate matter removal efficiency as high as the commercial N95 filter due to a combination of physical sieving and electrostatic adsorption.